Ethical Reasoning During a Pandemic: Results of a Five Country European Study. Issue 2 (3rd April 2022) - Johnson, S. B.; Lucivero, F.; Zimmermann, B. M.; Stendahl, E.; Samuel, G.; Phillips, A.; Hangel, N.
Abstract: Introduction: There has been no work that identifies the hidden or implicit normative assumptions on which participants base their views during the COVID-19 pandemic, and their reasoning and how they reach moral or ethical judgements. Our analysis focused on participants' moral values, ethical reasoning and normative positions around the transmission of SARS-CoV-2.Methods: We analyzed data from 177 semi-structured interviews across five European countries (Germany, Ireland, Italy, Switzerland and the United Kingdom) conducted in April 2020.Results: Findings are structured in four themes: ethical contention in the context of normative uncertainty; patterns of ethical deliberation when contemplating restrictions and measures to reduce viral transmission; moral judgements regarding "good" and "bad" people; using existing structures of meaning for moral reasoning and ethical judgement.Discussion: Moral tools are an integral part of people's reaction to and experience of a pandemic. 'Moral preparedness' for the next phases of this pandemic and for future pandemics will require an understanding of the moral values and normative concepts citizens use in their own decision-making. Three important elements of this preparedness are: conceptual clarity over what responsibility or respect mean in practice; better understanding of collective mindsets and how to encourage them; and a situated, rather than universalist, approach to the development of normative standards.